Deconstruction Of The Women’s Roles In “The Hunger Games” Film By Gary Ross - mislan mislan; bahren bahren; abkoriah (English Literature Department, Adab and Humanities Faculty, 2019)
This paper discusses deconstruction of the role of women in The Hunger Games film. The purpose of this thesis is; 1) to know what the roles of the women in The Hunger Games film, 2) to analyze how deconstruction of the roles of women in The Hunger Games film, and 3) to discover the effects that the result from deconstruction of the roles of the women in The Hunger Games film. In writing of this paper, the writer uses deconstruction theory and post-structuralist approach to support the theory. The writer uses descriptive qualitative method to analyze the problems there in. The data were taken from the primary data, namely The Hunger Games film in 2012 by Gary Ross. In this paper, the writer found some women’s roles at different roles in general in The Hunger Games film. Their roles are equal to the roles of men, they are; 1) from weak to strong, 2) dependent to independent, 3) timid to courageous, 4) emotional to rational, and 5) retarded to advanced. In this case, the deconstruction theory instrumental in eliminating the notion of women generally being a new and different assumption.